Thermal effect on mechanical properties of metakaolin-based engineered geopolymer composites (EGC) - Zhigang Zhang; Jianqiao Yu; Fengjiang Qin; Feng Sun (Case Studies in Construction Materials, 2023)
In this paper, a highly ductile PE fiber reinforced engineered geopolymer composites (EGC) was developed with metakaolin as main ingredient, and the mechanical properties of EGC after thermal exposures were investigated experimentally. The results showed that the compressive strength of EGC was gradually increased to 78.2 MPa as exposure temperature increased to 140 ℃ from 54.7 MPa at ambient environment, while it reduced to 72.0 MPa at 200 ℃ probably due to the voids left by melted fiber and formation of micro-cracks on specimens. In addition, thermal exposures likely refined the microstructures of EGC within 20–140 ℃. However, as the exposure temperature exceeds to 400 ℃, EGC completely loss its strength performance because of the severely cracking. Under tensile/flexural loadings, the EGC behaved high ductility within 20–140 ℃, and the tensile and flexural properties of EGC exhibited the similar tendency, that is, the strength and deformability increased gradually as exposure temperature increased from 20 ℃ to 120 ℃, and then appears a slight reduction at 140 ℃. For instance, the tensile strength and strain capacity of EGC was increased to 7.29 MPa and 5.18% at 120 ℃ as compared with 6.20 MPa and 3.73% that at 20 ℃, respectively; at 140 ℃, the value was decreased to 5.55 MPa and 4.15%, respectively, but was still comparable to that of 20 ℃ scenario. Moreover, the thermal exposures likely widen crack width on EGC howbeit retaining within 80 µm even the exposure temperature approaches the melting point of PE fiber.